Analysis of Student Learning Needs in the Differentiated Learning Review of Merdeka Curriculum in Physics Learning - Putra Prima, Wysnu Anggata; Khusaini, Khusaini; Hidayat, Arif (Universitas Papua, Jurusan Pendidikan Fisika FKIP Unipa, 2024)
This research aims to determine students' needs in studying physics material about Newton's Laws. Respondents consisted of 149 students and three physics teachers spread across schools within Malang Regency High School and Malang City High School. This research uses an explanatory sequential approach, quantitative data in the form of a questionnaire with respondents selected using a random sampling technique, then qualitative data in the form of a questionnaire with respondents selected using a purposive sampling technique. The instruments used were questionnaires and questionnaire guidelines. This research uses analysis by coding and grouping respondents' answers. In this research, it was found that there are various learning needs of students which are divided into three categories. Learning needs by learning grouping category are 6% of students who like the reading and writing learning model, 35.6% of students who like the audio-visual learning model, and 49% of students who like the kinesthetic learning model. It is hoped that the results of this research will provide follow-up in implementing learning that takes into account the learning needs of students that have been found in this research.